2014
DOI: 10.11118/actaun201462051087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cutting Pattern and Fertilization Level on Species Diversity and Evaluation of Grassland Quality

Abstract: Abstract) were combined with four treatments of exploitation intensity (4 cuts per year, fi rst cut on 15 th May, every next a er 45 days; 3 cuts per year, fi rst cut on 30 th May, every next a er 60 days; 2 cuts per year, fi rst cut on 15 th June, next a er 90 days; 2 cuts per year, fi rst cut on 30 th June, next a er 90 days). Numbers of species, Simpson's diversity index and evaluation of grassland quality according to Novák (2004) were evaluated. Numbers of species and Simpson's diversity index were signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
1
Order By: Relevance
“…Contrary to the assumption that alluvial grassland target species number decreases under nitrogen fertilization according to species richness [33,95], there was no decline during the 8-year study period. This is in accordance with the Steinach grassland experiment, the results of which concluded that species composition in productive alluvial grasslands is substantially less affected by fertilizer application than in low-productivity grasslands [36].…”
Section: Target Species Number and Target Forbs Covercontrasting
confidence: 75%
“…Contrary to the assumption that alluvial grassland target species number decreases under nitrogen fertilization according to species richness [33,95], there was no decline during the 8-year study period. This is in accordance with the Steinach grassland experiment, the results of which concluded that species composition in productive alluvial grasslands is substantially less affected by fertilizer application than in low-productivity grasslands [36].…”
Section: Target Species Number and Target Forbs Covercontrasting
confidence: 75%